Chemical Castration as a Sanction for Pedophilia Offenders: An Examination of Maqasid Sharia and the Principle of Human Rights Non-Discrimination - Atifah, Nurul Rezeki; Marilang, Marilang; Hamsir, Hamsir (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This article contains an analysis of chemical castration punishment from the perspective of human rights and Islamic criminal law. The main problem is related to how chemical castration can have a deterrent effect on perpetrators of sexual crimes, how the concept of chemical castration as a preventive measure for perpetrators of sexual crimes and how chemical castration is viewed from the perspective of human rights and Islamic law. In general, this research wants to explain the effectiveness of chemical castration which is used as a solution by the government in response to emergency warnings of sexual violence occurring in society. The author found that chemical castration was rejected on many fronts for various reasons. This research uses a type of library research with an exploratory research approach. The results found that chemical castration cannot provide a deterrent effect on the perpetrator and also cannot prevent potential pedophiles from committing pedophilic acts. From the perspective of human rights and Islamic law, they have the same view, both do not allow chemical castration injections on perpetrators of criminal offenses. From these results, it is also assumed that chemical castration cannot be used as a solution for those that touch the roots.